The Development of Electronic Student Worksheets on the Concept of Animalia to Improve High School Level Critical Thinking Skills - Feby Tiara Noor Kharisma; Muhammad Zaini; Kaspul Kaspul (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The development of the 21st century is marked by the development of technology and information, one example is the use of electronic Student Worksheets, which usually use paper worksheets, now we can find on the internet. Electronic Student Worksheets has become one of the essential learning technologies, especially during the current COVID-19 pandemic. This study aims to describe the validity, practicality, and effectiveness of electronic LKPD expectations on the concept of Animalia. Students are expected to be able to improve critical thinking skills through the implementation of electronic LKPD in the learning process. The research method used Tessmer's Formative Evaluation design, through stages 1) self-evaluation; 2) expert review; 3) one-to-one evaluation; and 4) small group evaluation. Data obtained from the research instrument in the form of an assessment sheet of validity and practicality of expectations. The results of research on the development of electronic LKPD are include in the valid category with a score of 3.78, the practicality of expectations is included in the very good category with a percentage score of 95.54%, and the effectiveness of expectations is included in the very good category on critical thinking skills of interpretation, evaluation, explanation, and self-regulation, while aspects of analysis and inference have increased to very good.AbstrakPerkembangan abad ke-21 ditandai dengan berkembangnya teknologi dan informasi, salah satu contohnya adalah penggunaan LKPD elektronik, yang biasanya LKPD menggunakan kertas sekarang dapat kita jumpai di internet. LKPD elektronik menjadi salah satu teknologi pembelajaran yang esensial, terlebih saat kondisi pandemi Covid-19 saat ini. Tujuan penelitian ini mendeskripsikan validitas, kepraktisan harapan, dan keefektifan LKPD elektronik konsep Animalia. Peserta didik diharapkan mampu untuk meningkatkan keterampilan berpikir kritis melalui implementasi LKPD elektronik dalam proses pembelajaran. Metode penelitian memakai desain Tessmer, terdiri atas: 1) self-evaluation; 2) expert review; 3) one-to-one evaluation; 4) small group evaluation. Data diperoleh dari instrumen penelitian berupa lembar penilaian validitas dan kepraktisan harapan LKPD elektronik. Hasil penelitian pengembangan LKPD elektronik termasuk dalam kategori valid dengan skor 3,78, kepraktisan harapan termasuk dalam kategori sangat baik dengan skor persentase 95,54%, serta keefektifan harapan termasuk dalam kategori sangat baik pada keterampilan berpikir kritis interpretasi, evaluasi, eksplanasi, dan pengaturan diri, sedangkan aspek analisis dan inferensi mengalami peningkatan menjadi sangat baik.